2019
DOI: 10.1111/pedi.12885
|View full text |Cite
|
Sign up to set email alerts
|

Increasing burden of type 2 diabetes in Navajo youth: The SEARCH for diabetes in youth study

Abstract: Aim SEARCH has recently reported that both prevalence and incidence of youth onset type 2 diabetes (YT2D) increased among most US race/ethnic groups in the early 2000s. This study reports on the incidence (2002‐2013) and prevalence (2001, 2009) of YT2D in the Navajo Nation among youth age < 20 years from 2001 to 2013. Methods SEARCH sought to identify prevalent YT2D cases in 2001 (N = 75) and 2009 (N = 70) and all incident YT2D cases in three periods: 2002 to 2005 (N = 53), 2006 to 2009 (N = 68), and 2010 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Traditionally, the Navajo people lived a healthy lifestyle characterized by physical activity and consumption of healthy, traditional foods. However, a combination of poverty [1], inadequate and discriminatory policies and disruptions in food systems [3] have led to high rates of food insecurity [4] and nutrition-related chronic diseases such as type 2 diabetes [5,6]. Currently, similar to many American Indian/ Alaskan Native (AI/AN) people, the Navajo experience limited access to healthy foods.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the Navajo people lived a healthy lifestyle characterized by physical activity and consumption of healthy, traditional foods. However, a combination of poverty [1], inadequate and discriminatory policies and disruptions in food systems [3] have led to high rates of food insecurity [4] and nutrition-related chronic diseases such as type 2 diabetes [5,6]. Currently, similar to many American Indian/ Alaskan Native (AI/AN) people, the Navajo experience limited access to healthy foods.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to many indigenous communities, 2 Western influences have resulted in dietary changes and an increasingly sedentary lifestyle, 3 increasing risk for many common chronic conditions such as type 2 diabetes. 4 In 2014, the Diné Food Policy Institute published a report making the case to "Rebuild a Self-Sufficient Food System for the Diné People." The report found that in most communities, there was farming of traditional foods and a strong interest in traditional food consumption, but high rates of poverty, food insecurity, food-related chronic illness, and only 10 full-service grocery stores on the Navajo Nation, an area the size of West Virginia.…”
mentioning
confidence: 99%
“…Both are related to a higher risk of type 2 diabetes and cardiovascular disease and hence COVID-19 morbidity and mortality. It is postulated that Obesity may slightly reduce the chances of COVID-19 infection through lower tidal volumes of gas exchange in the lungs [43][44][45][46][47].…”
Section: Covid-19 Cellular Pathogenesismentioning
confidence: 99%